Accelerated sarcopenia precedes learning and memory impairments in the P301S mouse model of tauopathies and Alzheimer's disease - Savannah Longo; María Laura Messi; Zhong‐Min Wang; William Meeker; Osvaldo Delbono (Wiley, 2024)
Abstract Background Alzheimer's disease (AD) impairs cognitive functions and peripheral systems, including skeletal muscles. The PS19 mouse, expressing the human tau P301S mutation, shows cognitive and muscular pathologies, reflecting the central and peripheral atrophy seen in AD. Methods We analysed skeletal muscle morphology and neuromuscular junction (NMJ) through immunohistochemistry and advanced image quantification. A factorial Analysis of Variance assessed muscle weight, NCAM expression, NMJ, myofibre type distribution, cross‐sectional areas, expression of single or multiple myosin heavy‐chain isoforms, and myofibre grouping in PS19 and wild type (WT) mice over their lifespan (1-12 months). Results Significant weight differences in extensor digitorum longus (EDL) and soleus muscles between WT and PS19 mice were noted by 7-8 months. For EDL muscle in females, WT weighed 0.0113 ± 0.0005 compared with PS19's 0.0071 ± 0.0008 (P < 0.05), and in males, WT was 0.0137 ± 0.0001 versus PS19's 0.0069 ± 0.0006 (P < 0.005). Similarly, soleus muscle showed significant differences; females (WT: 0.0084 ± 0.0004; PS19: 0.0057 ± 0.0005, P < 0.005) and males (WT: 0.0088 ± 0.0003; PS19: 0.0047 ± 0.0004, P < 0.0001). Analysis of the NMJ in PS19 mice revealed a marked reduction in myofibre innervation at 5 months, with further decline by 10 months. NMJ pre‐terminals in PS19 mice became shorter and simpler by 5 months, showing a steep decline by 10 months. Genotype and age strongly influenced muscle NCAM immunoreactivity, denoting denervation as early as 5-6 months in EDL muscle Type II fibres, with earlier effects in soleus muscle Type I and II fibres at 3-4 months. Muscle denervation and subsequent myofibre atrophy were linked to a reduction in Type IIB fibres in the EDL muscle and Type IIA fibres in the soleus muscle, accompanied by an increase in hybrid fibres. The EDL muscle showed Type IIB fibre atrophy with WT females at 1505 ± 110 μm2 versus PS19's 1208 ± 94 μm2, and WT males at 1731 ± 185 μm2 versus PS19's 1227 ± 116 μm2. Similarly, the soleus muscle demonstrated Type IIA fibre atrophy from 5 to 6 months, with WT females at 1194 ± 52 μm2 versus PS19's 858 ± 62 μm2, and WT males at 1257 ± 43 μm2 versus PS19's 1030 ± 55 μm2. Atrophy also affected Type IIX, I + IIA, and IIA + IIX fibres in both muscles. The timeline for both myofibre and overall muscle atrophy in PS19 mice was consistent, indicating a simultaneous decline. Conclusions Progressive and accelerated neurogenic sarcopenia may precede and potentially predict cognitive deficits observed in AD.